PENERAPAN TEKNOLOGI AMONIASI JERAMI SEBAGAI PAKAN ALTERNATIF SAPI POTONG DI KENAGARIAN SUNGAI KUNYIT, SOLOK SELATAN - Ferry Lismanto Syaiful; Dewa Tirta Diva; Mahdiatul Hafizoh (Jurnal Hilirisasi IPTEKS, 2020)
The feed is an essential requirement in cattle farming. The need for cattle feed reaches 80% of the cost of raising livestock. To reduce the cost of this feed, we need an alternative feed at a low price. Ammonia straw is one way to process agricultural waste products into alternative feed used for beef cattle feed. This ammonia feed technology is an efficient method for improving the quality of straw as animal feed. The objectives of this activity are 1. to increase the knowledge and understanding of cattle breeders in the use of straw waste as an alternative feed for cattle for feed cost efficiency, 2. to increase the productivity of cattle through straw ammonia feed technology, and 3. to increase the welfare of breeders by utilizing rice straw waste as feed. Livestock. The method used in this activity is counseling, demonstration of straw ammonia, and evaluating the application of straw ammonia technology as an alternative feed source for breeders. The extension method is carried out by giving lectures on the use and processing of straw waste as animal feed. Meanwhile, a demonstration of processing straw waste as ammoniated feed. The targets of this activity are farmers and the community in Kenagarian Sungai Kunyit. The results obtained from this activity, activity participants can gain knowledge and understanding in processing ammonia feed as an alternative feed. The use of ammonia feed can overcome the shortage of animal feed in the dry season/famine, overcoming environmental pollution from agricultural waste/straw. Ammoniated straw feed can also increase the digestibility of livestock so that it can increase livestock productivity. Cattle farmers in Kenagarian Sungai Kunyit can make their straw ammonia feed. Ammoniated feed can reduce feed costs, and livestock is more profitable.